PENGARUH UKURAN PERUSAHAAN DAN RETURN ON EQUITY (ROE) TERHADAP NILAI PERUSAHAAN SUB SEKTOR ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Fitratul Aqidah; M. Rimawan; Nafisah Nurulrahmatiah (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to determine the effect of Company Size and Return On Equity (ROE) on the Company Value of the Cigarette Sub-Sector listed in Indonesia Stock Exchange for the period 2019-2021. Variables to measure company size are LN (Total Assets), the variable Return On Equity (ROE) measured by Net Income / Total Equity, the variable used to measure Company Value is PBV (price per share). The population of this study is companies in the manufacturing sector of the Cigarette subsector listed on the IDX for the 2019-2021 period with a total of 5 companies. Using the purposive sampling method, a sample of 4 companies was taken. The analysis techniques used are multiple linear regression analysis and hypothesis tests and also classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, with an alpha signification level of 5%. The results showed that the variable Company Size (Ln) did not have a significant effect on Company Value (PBV) and ROE was not significant on company value, while company size and ROE did not simultaneously affect company value